A study of load balancing algorithm for multiple runway airports - Lim, Wei Jie (2015)
Singapore’s Changi International airport is currently facing runway capacity constraints with global air traffic growth. Therefore, efficient use of this limited resource is crucial to cope with the rising demand as well as ensuring efficient air traffic operations. The objective of this research is to analyze on the existing load balancing strategies and propose an improved load-balancing algorithm for multiple runways under mixed-mode operations. The paper presents a mixed-integer formulation for scheduling a set of aircrafts that consist of arriving and departing flights. The objective function is to minimize the overall cost for the formulated model. The load balancing algorithm will be implemented by using the current Changi dual parallel runway configuration data as a test bed. The model was solved using General Algebraic Modeling System (GAMS) over several simulated instances of up to 90 flight movements per hour. The computational results were obtained in a short time, which was satisfactory in comparison with several existing load balancing strategies that were far apart from optimality in most cases.